LIFE CYCLE ASSESSMENT OF DIRECT AND EXTRUSION SPINNING: A CASE STUDY - Altun, Şule; Akal-Solmaz, Seval Kutlu; Ustun, Gokhan Ekrem; Kagnici, Ismail (Parlar Scientific Publications (P S P), 2018)
This study assessed the status of direct and extrusion spinning in Bursa, Turkey. Sensitivity analysis of Life Cycle Assessment (LCA) methods and dominant processes were conducted to validate the results. The results of this study increase the life cycle inventory database for Poly(ethylene terephthalate) (PET) fibre production, provide basic and necessary information for evaluating environmental impacts of international chemical products, and facilitate the decision making of policymakers regarding the establishment, reconstruction, expansion, or technological transformation of industries. However, the combined assessment of economic, social and management factors warrants further research to provide a more systematic and sustainable assessment.
Keywords: Environmental impact; Life cycle assessment; PET fibre production; Spinning